The Deuteronomistic Endorsement of Sacrificing Errant Individuals as Reflected by the Hebrew Terms Ḥērem and Biʽēr. (2nd September 2020) - Tatlock, Jason
Abstract: Despite the efforts of some scholars, biblical denunciations of one form of human sacrifice cannot be taken as condemnations of all types. Thus, while the writers of the Deuteronomistic History clearly regarded the slaying of children at the Jerusalem Tophet adversely, they accepted the legitimacy of sacrificing religiously errant individuals like murderers and others who went against their form of Yahwism. Such an endorsement is particularly represented by the biblical Hebrew ideas of sacrificial dedication (ḥērem) and burning up/consuming contamination (biʽēr). In the wake of Judah's fall and Jerusalem's destruction, the Deuteronomists promoted human sacrifice as a means to maintain or establish the purity of the Israelite community and the land of Canaan while delineating the limits of their version of a Yahwistic group.